Aligned Networks of Engineered Fibrillar Fibronectin Guide Cellular Orientation and Motility. Issue 6 (1st March 2021) - Neale, Dylan B.; Muñiz, Ayşe J.; Jones, Michael S.; Kim, Do Hoon; Buschhaus, Johanna M.; Humphries, Brock A.; Wang, William Y.; Baker, Brendon M.; Raymond, Jeffery E.; Solorio, Luis; Luker, Gary D.; Lahann, Joerg
Abstract : The extracellular matrix (ECM) influences biological processes associated with tissue development and disease progression. However, robust cell‐free techniques to control fiber alignment of naturally derived ECM proteins, such as fibronectin (Fn), remain elusive. It is demonstrated that controlled hydrodynamics of Fn solutions at the air/fluid interface of porous tessellated polymer scaffolds (TPSs) generates suspended 3D fibrillar networks with alignment across multiple length scales (<1, 1–20 μm, extended to >1 mm). The direction of the fluid flow and the architecture of the polymeric supports influence protein solution flow profiles and, subsequently, the alignment of insoluble Fn fibrils. Aligned networks of fibrillar Fn characteristically alter fibroblast phenotype, indicated by increased directional orientation, enhanced nuclear and cytoskeletal polarity, and highly anisotropic and persistent cell motility when compared with nonaligned 3D networks and 2D substrates. Engineered extracellular matrices (EECMs) establish a critically needed tool for both fundamental and applied cell biology studies, with potential applications in diverse areas such as cancer biology and regenerative medicine. Abstract : Herein, the production of highly aligned 3D fibrillar fibronectin (Fn) networks suspended across hyperporous polymeric scaffold supports described. Orientation of 3D protein networks is achieved through control of the fluid‐flow profiles across the scaffold supports at the air–protein solution interface during hydrodynamically induced fibrillogenesis in the absence of solution denaturants or harsh solvents. Relative to nonaligned substrates of the same composition, aligned networks promote highly directionally persistent fibroblast migration.